Challenges, strategies and consequences from the perspective of German nursing home managers during the first wave of the COVID-19 pandemic: a qualitative interview study - Sander, Marco; Dano, Richard; Bieber, Anja Martha; Dammermann, Anna; Fleischer, Steffen; Dinand, Claudia; Müller, Martin; Möhler, Ralph; Schultes, Kristin; Köpke, Sascha; Dichter, Martin N.; Hoffmann, Falk; et al. (BMC geriatrics, 2023)
COVID-19, Nursing homes, Qualitative study, Challenges, Strategies, Consequences